THE MODERN VIEW OF THE MANAGEMENT OF PREGNANCY IN HIV INFECTION - I. O. Makarov; T. V. Shemanaeva (Акушерство, гинекология и репродукция)
Transmission of HIV from mother to child can occur during pregnancy, at childbirth and in the postpartum period when breastfeeding. The risk of transmission of HIV from mothers to their children depends on the stage of the mother’s disease. The use of chemoprophylaxis with the mother during pregnancy and childbirth, after the birth the child, reduces vertical transmission.